2017
DOI: 10.1002/solr.201700174
|View full text |Cite
|
Sign up to set email alerts
|

Toward High‐Performance Polymer Photovoltaic Devices for Low‐Power Indoor Applications

Abstract: This article describes the performance of organic photovoltaic (OPV) devices, incorporating three different polymer/fullerene derivative blends, under low‐level lighting conditions. The devices exhibit much higher power conversion efficiencies (PCEs) under indoor lighting conditions than they do under sunlight. The best‐performing device is capable of delivering a power output of 22.57 μW cm−2, corresponding to a PCE of 13.76%, under illumination with indoor lighting conditions at 500 lux. Increasing the open‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 21 publications
0
50
0
Order By: Relevance
“…A typical fullerene-based OPV has been reported to exceed a PCE of 10% under a simulated indoor light source. [33][34][35][36][37][38][39] Also, the SiNC-HPVs can be a potential energy harvesting device for indoor IoT applications.…”
Section: Device Performance Under Standard Indoor Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical fullerene-based OPV has been reported to exceed a PCE of 10% under a simulated indoor light source. [33][34][35][36][37][38][39] Also, the SiNC-HPVs can be a potential energy harvesting device for indoor IoT applications.…”
Section: Device Performance Under Standard Indoor Lightmentioning
confidence: 99%
“…[28][29][30] In recent years, due to the rapid development of IoT (Internet of Things) related technology, the number of IoT devices has dramatically increased. 31,32 Many type of printable PV devices such as OPVs, [33][34][35][36][37][38][39][40][41][42] dye-sensitized solar cells 43,44 and perovskite solar cells 45,46 have been explored for indoor applications, OPVs are especially expected to be used as an energy harvesting system for IoT devices because of their potential for low power operation, independent and distributed applications, high portability and device designability. In this study, we successfully demonstrated SiNC-HPVs with PCE as high as 9.7% and power density of 34.0 mW cm À2 under standard indoor light irradiation (1000 lx).…”
Section: Introductionmentioning
confidence: 99%
“…Organic photovoltaic (OPV) devices have been attracting much attention because of their advantageous properties, including light weight, mechanical flexibility, low material and fabrication cost, and short energy payback times [1][2][3][4]. Apart from traditional solar panels, possible applications of OPV devices also include power generators for wearable electronics, portable devices, and the Internet of things (IoTs) [5][6][7][8][9][10]. The state-of-the-art OPV devices are prepared based on the concept of "bulk heterojunction."…”
Section: Introductionmentioning
confidence: 99%
“…where ݊ is the ideality factor, ݇ is the Boltzmann constant, ܶ is the absolute temperature, ‫ݍ‬ is the elementary charge, ‫ܫ‬ is the photocurrent, and ‫ܫ‬ is the dark current. [11] From Eq. 1, there are two main observations: (1) an OPV device with a small dark current gives rise to a large V oc .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to achieve a large V oc at ambient lights, a BHJ that gives a large V oc under 1-Sun is essential. [11,12] high PCEs, the porphyrin-based BHJ cells also exhibit superior performances under thick films (~200nm) and enhanced stabilities. The origins of these superior properties were examined, and they can be attributed to low electronic disorders of these materials when compared to their polymer counterparts.…”
Section: Introductionmentioning
confidence: 99%